Hemoglobin Genotypes Modulate Inflammatory Response to Plasmodium Infection - Harp, Keri Oxendine; Botchway, Felix; Dei-Adomakoh, Yvonne; Wilson, Michael D.; Hood, Joshua L.; Adjei, Andrew A.; Stiles, Jonathan K.; Driss, Adel (Frontiers in Immunology, 2020)
In 2018, 228 million cases and 405,000 malaria-associated deaths were reported worldwide with a majority being in Africa. A wide range of factors, including parasitemia, host immunity, inflammatory responses to infection, and host hemoglobin genotype, mediate the severity of malaria. Among the hemoglobinopathies, hemoglobin S (HbS) is caused by a single amino acid substitution of Glutamic Acid replaced by Valine at the sixth position of the beta-globin chain (E6V). Hemoglobin C (HbC) on the other hand, involves a single amino acid substitution of Glutamic Acid by a Lysine (E6K), which has received the most attention. These substitutions alter the stability of Hb leading to wide-ranging hematological disorders. The homozygous state of hemoglobin S (HbSS) results in sickle cell anemia (SCA) whereas the heterozygous state (HbAS) results in sickle cell trait (SCT). Both mutations are reported to mediate the reduction in the severity and fatality of Plasmodium falciparum malaria. The mechanism underlying this protection is poorly understood. Since both malaria and sickle cell disease (SCD) are associated with the destruction of erythrocytes and widespread systemic inflammation, identifying which inflammatory factor(s) mediate susceptibility of individuals with different hemoglobin genotypes to Plasmodium infection could result in the discovery of new predictive markers and interventions against malaria or SCD severity. We hypothesized that hemoglobin genotypes modulate the inflammatory response to Plasmodium infection. We conducted a cross-sectional study in Ghana, West Africa, between 2014 and 2019 to ascertain the relationships between blood inflammatory cytokines, Plasmodium infection, and hemoglobin genotype. A total of 923 volunteers were enrolled in the study. A total of 74, age and sex-matched, subjects were identified with various genotypes including HbAS, HbAC, HbSS, HbSC, HbCC or HbAA. Complete blood counts and serum inflammatory cytokine expression levels were assessed. The results indicate that differential expression of CXCL10, TNF-α, CCL2, IL-8, and IL-6 were tightly linked to hemoglobin genotype and severity of Plasmodium infection and that these cytokine levels may be predictive for susceptibility to severe malaria or SCD severity.